1998
DOI: 10.1002/(sici)1097-4695(199810)37:1<69::aid-neu6>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

When, where, and how much? Expression of the Kv3.1 potassium channel in high-frequency firing neurons

Abstract: The Kv3.1 potassium channel gene is expressed in neurons that fire action potentials at high frequencies. Neurons that express this gene, such as auditory brain stem neurons, have high‐threshold voltage‐dependent potassium currents that activate and deactivate unusually rapidly, and whose characteristics match those of the Kv3.1 subunit expressed heterologously. The level of Kv3.1 expression in neurons is regulated during development and by environmental stimuli. Pharmacological and computer modeling studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…Kv3.1 subunits are widely expressed, particularly in neurons that fire action potentials at high frequencies, including those in the auditory brainstem and cerebellum (Gan and Kaczmarek 1998). Kv3.1-containing channels deactivate very rapidly after a depolarizing pulse, an important feature thought to enable action potentials to occur in rapid succession.…”
Section: Resultsmentioning
confidence: 99%
“…Kv3.1 subunits are widely expressed, particularly in neurons that fire action potentials at high frequencies, including those in the auditory brainstem and cerebellum (Gan and Kaczmarek 1998). Kv3.1-containing channels deactivate very rapidly after a depolarizing pulse, an important feature thought to enable action potentials to occur in rapid succession.…”
Section: Resultsmentioning
confidence: 99%
“…Auditory-specific specializations are not unexpected when considering the demands of conveying rapidly occurring sound signals into the brain (Gan and Kaczmarek, 1998;Oertel, 1999;Trussell, 1999), especially for the high frequency spiral ganglion neurons. The functional significance of a presumptive increase in AMPAR density in the postsynaptic membrane of basal spiral ganglion neurons may be compensatory; to counteract the greater density of voltage-gated ion channels that they possess and the resultant decrease in input resistance during depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at least in the neocortex and hippocampus, PVB-IR neurons ensheathed by PNN have been shown to express Kv3.1b (Sekirnjak et al, 1997;Gan and Kaczmarek, 1998;Hartig et al, 1999), a subunit of voltagegated potassium channels that, like PNNs, has been found to be associated with highly active neurons (Perney et al, 1992;Lenz et al, 1994;Weiser et al, 1995;Gan and Kaczmarek, 1998). PVB-IR neurons are in fact characterized electrophysiologically as "fast-spiking".…”
Section: Relationship Between Pvb and Pnns In The Human Amygdalamentioning
confidence: 99%
“…Other molecules preferentially expressed by these neurons are also involved in such specific functions. For instance, expression of the alpha 1subunit of the GABA A receptor in amygdalar PVB-IR neurons confers on these receptors specific kinetic properties that may be important for oscillatory activity (McDonald and Mascagni, 2004), and the Kv3.1b subunit of voltagegated potassium channels has been proposed to be necessary for the generation of the high firing rates typical of these neurons (Perney et al, 1992;Lenz et al, 1994;Weiser et al, 1995;Gan and Kaczmarek, 1998).…”
mentioning
confidence: 99%